Emodin promotes the recovery of rheumatoid arthritis by regulating the crosstalk between macrophage subsets and synovial fibroblast subsets - Lianying Cheng; Xiaofeng Rong (Animal Models and Experimental Medicine)
Abstract Background To study the relationships among emodin, synovial fibroblasts (FLSs), and macrophages (STMs) to provide guidance for the use of emodin in rheumatoid arthritis (RA) treatment. Methods RA clinical samples from patients with different pathological processes were collected, and the correlations between the subsets of FLSs and STMs and pathological processes were analyzed via flow cytometry. In vitro experimental methods such as enzyme linked immunosorbent assay (ELISA), Western blotting, Transwell assays, CCK‐8 assays and cell coculture were used to assess cell proliferation, migration and secretion of inflammatory factors. A collagen‐induced arthritis mouse model was constructed to investigate the therapeutic potential of emodin in RA by flow cytometry, micro‐CT and staining. Results Unique subsets of FLSs and STMs, namely, FAPα+THY1− FLSs, FAPα+THY1+ FLSs, and MerTKposTREM2high STMs, were identified in synovial tissues from RA patients. The number of MerTKposTREM2high STMs was negatively correlated with the degree of damage in RA, while the number of FAPα+THY1− FLSs was positively correlated with damage. On the one hand, emodin promoted the aggregation of MerTKposTREM2high STMs. Moreover, MerTKposTREM2high STM‐mediated secretion of exosomes was promoted, which can inhibit the secretion of pro‐inflammatory factors by FAPα+THY1+ FLSs and promote the secretion of anti‐inflammatory factors by FAPα+THY1+ FLSs, thereby inhibiting FAPα+THY1−FLS proliferation and migration, improving the local immune microenvironment, and inhibiting RA damage. Conclusion Emodin was shown to regulate the aggregation of STM subsets and exosome secretion, affecting the secretion, proliferation and migration of inflammatory factors in FLS subsets, and ultimately achieving good therapeutic efficacy in RA patients, suggesting that it has important clinical value.